Cu2O Nanoparticles with Both {100} and {111} Facets for Enhancing the Selectivity and Activity of CO2 Electroreduction to Ethylene. Issue 6 (30th January 2020) - Gao, Yugang; Wu, Qian; Liang, Xizhuang; Wang, Zeyan; Zheng, Zhaoke; Wang, Peng; Liu, Yuanyuan; Dai, Ying; Whangbo, Myung‐Hwan; Huang, Baibiao
Abstract: Cu2 O nanoparticles (NPs) enclosed with different crystal facets, namely, c‐Cu2 O NPs with {100} facets, o‐Cu2 O NPs with {111} facets, and t‐Cu2 O NPs with both {111} and {100} facets, are prepared and their electrocatalytic properties for the reduction of CO2 to C2 H4 are evaluated. It is shown that the selectivity and activity of the C2 H4 production depend strongly on the crystal facets exposed in Cu2 O NPs. The selectivities for the C2 H4 production increases in the order, c‐Cu2 O < o‐Cu2 O < t‐Cu2 O, (with FEC2H4 = 38%, 45%, and 59%, respectively). This study suggests that Cu2 O NPs are more likely responsible for the selectivity and activity for the C2 H4 production than the metallic Cu NPs produced on the surface of Cu2 O NPs. This work provides a new route for enhancing the selectivity of the electrocatalytic CO2 reduction by crystal facet engineering. Abstract : The selectivity of CO2 electroreduction to ethylene can be greatly enhanced from Cu2 O nanoparticles with both {100} and {111} crystal facets exposed, which is ascribed to the better C–C coupling, ethylene desorption and multielectron transfer kinetics. This work provides a new route for enhancing the selectivity of the electrocatalytic reduction of CO2 to multicarbon products by crystal facet engineering.